2022
DOI: 10.1002/vetr.2282
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the association between blood genotype or phenotype and haemoplasma infection in UK and Italian cats

Abstract: Background: In humans, blood groups are associated with varying prevalence of infections. The aim of this study was to determine if associations exist between the feline AB blood group system and haemoplasma infection. Methods: Data from two studies were combined. In the first study, DNA samples from 131 haemoplasma-infected and 132 haemoplasma-uninfected UK cats underwent pyrosequencing to determine their blood genotype as AA, Ab or bb. In the second study, blood samples from 160 Italian cats of known blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Male gender, adult age, nonpedigree breed, outdoor access, blood genotype and coinfection with FIV and/or FeLV are associated with hemoplasmas positivity with conflicting results for some variables. 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 In the present study, a significant association was found for male gender and for FeLV positivity with Hemoplasma spp. qPCR positivity.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Male gender, adult age, nonpedigree breed, outdoor access, blood genotype and coinfection with FIV and/or FeLV are associated with hemoplasmas positivity with conflicting results for some variables. 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 In the present study, a significant association was found for male gender and for FeLV positivity with Hemoplasma spp. qPCR positivity.…”
Section: Discussionsupporting
confidence: 63%
“…Male sex, adult age, nonpedigree breed, outdoor access, blood genotype, and coinfection with retroviruses (feline immunodeficiency virus [FIV] and/or feline leukemia virus [FeLV]) are associated with Hemoplasma spp. PCR positivity 2,8‐20 . Hemoplasma spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation